Pengaruh Exchange Rate dan GDP Terhadap Ekspor dan Impor Indonesia - Adi, Lumadya (Universitas Dr. Soetomo, 2017)
The purpose this research is to examine the impact of Exchange Rate and GDP on Indonesia’s Export and Import. Tools analysis is Dynamics Ordinary Least Square (DOLS): Error Correction Model (ECM). The result are: 1. GDP influence positif and significant in short-term and longterm relationship on Indonesia’s impor; 2. Exchange Rate influence positif and significant in short-term and longterm relationship on Indonesia’s impor; 3. GDP influence positif and significant in short-term but negatif and significant in longterm relationship on Indonesia’s export; 4. Exchange rate influence positif and significant in short-term but negatif and significant in longterm relationship on Indonesia’s export.Keywords: error correction model, gdp, exchange rate, impor, ekspor